Lifestyle in older adults with type II diabetes mellitus in a housing complex in Lima - Pérez de Velazco Maravi, Carmen Rosa (2021)
Objectives: It was to determine the lifestyle in older adults with type II diabetes mellitus in a housing complex in Lima. Materials and methods: The present study was carried out from the perspective of the quantitative approach, its methodological design was correlational-cross-sectional. The population consisted of 82 participants. The data collection technique was the survey and the measurement instrument used was the Instrument to Measure Lifestyle or IMEVID, which presents 25 items and 7 dimensions. Results: Female participants represent 57.3% (n = 47) and male participants 42.7% (n = 35). The minimum age of the participants was 64 years, the maximum 86 years and the average age 73.5 years. Regarding the lifestyle in older adults, the unhealthy lifestyle predominated with 75% (n = 62), followed by unhealthy with 20.7% (n = 17) and healthy with 3.7% (n = 3). According to the dimensions, in nutrition the unhealthy lifestyle predominated with 58.5% (n = 48), in physical activity the healthy lifestyle with 40.2% (n = 33), in tobacco consumption the style of unhealthy life with 78% (n = 64), in alcohol consumption the unhealthy lifestyle with 72% (n = 59), in information about diabetes the unhealthy lifestyle with 46.3% (n = 38 ), in emotions the unhealthy lifestyle with 62.2% (n = 51) and finally in therapeutic adherence the healthy one with 65% (n = 54). Conclusions: In relation to the lifestyle in older adults, the unhealthy lifestyle predominated, followed by unhealthy and healthy.